A Cornucopia of Iridium Nitrogen Compounds Produced from Laser‐Ablated Iridium Atoms and Dinitrogen. Issue 33 (30th April 2020) - Stüker, Tony; Beckers, Helmut; Riedel, Sebastian
Abstract: The reaction of laser‐ablated iridium atoms with dinitrogen molecules and nitrogen atoms yield several neutral and ionic iridium dinitrogen complexes such as Ir(N2 ), Ir(N2 ) +, Ir(N2 )2, Ir(N2 )2 −, IrNNIr, as well as the nitrido complexes IrN, Ir(N)2 and IrIrN. These reaction products were deposited in solid neon, argon and nitrogen matrices and characterized by their infrared spectra. Assignments of vibrational bands are supported by ab initio and first principle calculations as well as 14/15 N isotope substitution experiments. The structural and electronic properties of the new dinitrogen and nitrido iridium complexes are discussed. While the formation of the elusive dinitrido complex Ir(N)2 was observed in a subsequent reaction of IrN with N atoms within the cryogenic solid matrices, the threefold coordinated iridium trinitride Ir(N)3 could not be observed so far. Abstract : Iridium and nitrogen : This work presents the last missing homoleptic dinitrogen and nitrido complexes of the platinum‐group metals and helps understanding the interaction of nitrogen with metals to facilitate nitrogen fixation. Dinitrogen activation, oxidation states and bond orders are discussed and give insight to the reactivity and electronic structure of these intriguing compounds.